Altered defaecatory behaviour and faecal incontinence in a video‐tracked animal model of pudendal neuropathy. (May 2017) - Devane, L. A.; Lucking, E.; Evers, J.; Buffini, M.; Scott, S. M.; Knowles, C. H.; O'Connell, P. R.; Jones, J. F. X.
Abstract: Aim: The aim was to develop a behavioural animal model of faecal continence and assess the effect of retro‐uterine balloon inflation (RBI) injury. RBI in the rat causes pudendal neuropathy, a risk factor for obstetric related faecal incontinence in humans. Method: Video‐tracking of healthy rats ( n  =   12) in a cage containing a latrine box was used to monitor their defaecatory behaviour index (DBI) over 2 weeks. The DBI (range 0–1) was devised by dividing the defaecation rate (pellets per hour) outside the latrine by that of the whole cage. A score of 0 indicates all pellets were deposited in the latrine. Subsequently, the effects of RBI ( n  =   19), sham surgery ( n  =   4) and colostomy ( n  =   2) were determined by monitoring the DBI for 2 weeks preoperatively and 3 weeks postoperatively. Results: The DBI for healthy rats was 0.1 ± 0.03 with no significant change over 2 weeks ( P  =   0.71). In the RBI group, 13 of 19 rats (68%) showed no significant change in DBI postoperatively (0.08 ±  −0.05 vs 0.11 ±  −0.07) while in six rats the DBI increased from 0.16 ±  −0.09 to 0.46 ± 0.23. The negative control, sham surgery, did not significantly affect the DBI (0.09 ± 0.06 vs 0.08 ± 0.04, P  =   0.14). The positive control, colostomy, increased the DBI from 0.26 ± 0.03 to 0.86 ± 0.08. Conclusions: This is the first study showing a quantifiable change in defaecatory behaviour following injury in an animal model. This model of pudendal neuropathy affects continence in 32% of rats and provides a basis for research on interventions for incontinence.